Future therapies: Early trials and basic science - Andersson, Karl-Erik (Canadian Urological Association Journal, 2013)
Pharmacotherapeutic options for overactive bladder (OAB) include antimuscarinics and the beta3-adrenoceptor (AR) agonist mirabegron. Research and development of novel therapeutic options for OAB continues to be an active field. This review summarizes recent research with the existing therapies as well as the most promising agents in development.